THE DEVELOPMENT OF INTERACTIVE MULTIMEDIA LEARNING IN VOCATIONAL SCHOOL - Radhiatul Husni; Ulva Rahmi; Miftahir Rizqa (UIR PRESS, 2023)
The purpose of this study is to develop the use of interactive multimedia learning in vocational schools in Indonesia. This learning media was used on material about diagnosing computer and peripheral operation problems and was developed by using the Instructional Development Institute (IDI) development method. This method included the following stages of the procedure: define, develop, and evaluate. Furthermore, the subject of this study was the first-grade students in SMK N 1 Hiliran Gumanti. The result showed that 1) The development of learning media based on interactive multimedia was considered valid based on the content by 5 experts of 91.80%; 2) Based on the responses of 28 students, interactive multimedia learning was proved to be more practical by 85.25%; 3) The use of effective multimedia learning improved student learning outcomes showed by an incline on students’ scores from 42.1% to 84.21%. Briefly, the development of interactive multimedia learning has proved to be valid, practical, and effective. This media learning can be used to enhance student learning outcomes related to the material about diagnosing computer and peripheral operation problems in the vocational school.